Carriage of the zoonotic organism Streptococcus suis in chicken flocks in Vietnam. (28th April 2020) - Nhung, Nguyen Thi; Yen, Nguyen Thi Phuong; Cuong, Nguyen; Kiet, Bach Tuan; Hien, Vo Be; Campbell, James; Thwaites, Guy; Baker, Stephen; Geskus, Ronald; Ashton, Philip; Carrique‐Mas, Juan
Abstract: Streptococcus suis infections are an emerging zoonotic agent causing severe disease in humans and a major pig pathogen worldwide. We investigated the colonization of S. suis in healthy chickens in different flocks ( n  = 59) as well as in‐contact pigs in farms with S. suis ‐positive chickens ( n  = 44) in the Mekong Delta of Vietnam. Streptococcus suis was isolated from 20 (33.9%) chicken flocks and from all pigs investigated. Chicken isolates formed a distinct genotypic cluster compared with pig and human strains, although two chicken isolates (10%) clustered with pig isolates. Chicken isolates had unusually high levels of resistance against tetracycline (100%), clindamycin (100%) and erythromycin (95%); and intermediate resistance against penicillin (35%) and ceftriaxone (15%). Our findings suggest that chickens may potentially represent a source of S. suis infection to in‐contact humans and pigs.